Proof‐of‐concept study of anti‐Fel d 1 IgY antibodies in cat food using the MASK‐air® app - Bousquet, Jean; Gherasim, Alina; Blay, Frédéric; Mathieu‐Dupas, Eve; Batot, Géraldine; Laune, Daniel; Sousa‐Pinto, Bernardo; Zuberbier, Torsten; Pham‐Thi, Nhân; Hofmann, Bernard; Urban‐Kraemer, Emilie; Nguyen‐Grosjean, Van‐Mai; et al. (Clinical and translational allergy, 2024)
Background An innovation to better manage cat‐allergic patients utilises anti‐Fel d 1 IgY antibodies to neutralise Fel d 1 after its production by the cat. However, there is no published study showing its clinical efficacy in humans in a home setting. A longitudinal, open‐label, proof‐of‐concept study was carried out to approach clinical efficacy of the cat food in cat‐allergic patients. Methods After a baseline evaluation, the cats ate only the cat food for the following 4 months. Daily evaluation of efficacy was performed for 2 weeks at baseline and after 1, 2 and 3 months of intervention for periods of 2 weeks. The MASK‐air app was used daily to assess symptoms, work productivity and medications. Results Of the 49 patients screened, 42 were followed up and 33 (78.5%) reported MASK‐air data at all 3 evaluation periods. The primary end point (visual analogue scale [VAS] for global allergy symptoms) was significantly improved (p < 0.0001). All symptoms (VAS nose, eye, and asthma), VAS work and the combined symptom‐medication score significantly improved after 1 month. The percentage of uncontrolled days (VAS>20/100) decreased from 64% at baseline to 35% at 1 month (p < 0.0001) and 14% at 3 months. A sensitivity analysis in patients with uncontrolled disease at baseline found similar results. Discussion A cat diet containing anti‐Fel d 1 antibodies was able to (i) show decreased allergic symptoms and related outcomes, (ii) inform the design and feasibility of future studies with a control arm and (iii) estimate the sample size of the study. Study registration number: clinicaltrials.gov: NCT05656482.